2012
DOI: 10.1029/2012ja017952
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh wave signature in ionograms induced by strong earthquakes

Abstract: [1] After the magnitude 9.0 earthquake off the Pacific coast of Tohoku (near the east coast of Honshu, Japan), which occurred on 11 March 2011, an unusual multiple-cusp signature (MCS) was observed in ionograms at three ionosonde stations across Japan. To investigate the general characteristics of MCSs, we examined ionograms obtained during the period 1957 to 2011 from five ionosonde stations in Japan after earthquakes with a seismic magnitude of 8.0 or greater. A total of 43 such earthquakes occurred after 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…Such highly deformed ionograms with slant satellite traces as examined in this paper are a rare occurrence. However, when previously examined coseismic ionogram disturbances after 1957 (Maruyama et al, 2012;Maruyama and Shinagawa, 2014) were revisited, a similar effect was identified in two ionograms obtained at ionosonde sites in Japan. Two ionograms were shown in Figs.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Such highly deformed ionograms with slant satellite traces as examined in this paper are a rare occurrence. However, when previously examined coseismic ionogram disturbances after 1957 (Maruyama et al, 2012;Maruyama and Shinagawa, 2014) were revisited, a similar effect was identified in two ionograms obtained at ionosonde sites in Japan. Two ionograms were shown in Figs.…”
Section: Resultsmentioning
confidence: 94%
“…These velocities yield an inclination of 8 • for the infrasound wavefronts. Vertical density gradients in the F1 region of the unperturbed ionosphere are critical for the formation of cusps in the ionogram trace (Maruyama et al, 2012). For realistic simulations of a perturbed ionogram, the background ionospheric profile was numerically produced and parameters in the following equations were determined to fit the synthesized ionogram with the observed ionogram without perturbation shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An OTH SuperDARN in Hokkaido, Japan, also detected the ionospheric disturbances caused by this earthquake (Nishitani et al, 2011). Conventional sensors such as ionosonde were also used to study the ionospheric disturbances (Liu and Sun, 2011;Maruyama et al, 2011Maruyama et al, , 2012.…”
Section: The Case Of the Great Sumatra-andaman Earthquakementioning
confidence: 99%
“…Rayleigh wave signatures in the ionosphere following earthquakes have been measured by Doppler sounding (e.g., Yuen et al 1969;Tanaka et al 1984;Artru et al 2004;Chum et al 2016) using TEC measurements (e.g., Ducic et al 2003;Astafyeva et al 2009;Rolland et al 2011) and the inspection of ionograms (Maruyama et al 2012(Maruyama et al , 2016a(Maruyama et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%